2015
DOI: 10.1016/j.jssc.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of MIIM′IV(PO4)2 double monophosphates

Abstract: a b s t r a c t M II M′ IV (PO 4 ) 2 compounds have been extensively studied for several decades for their potential applications in the field of several domains such as matrices for actinides conditioning, phosphors etc. In this paper, the relationships between composition and crystal structure of these compounds are established. A review of the various processes used for the synthesis of these compounds is also proposed, as well as their most reported properties. M II M′ IV (PO 4 ) 2 structures stem from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Diffraction lines with I obs < 1 are omitted. relationships between composition and crystal structure [20]. Indeed we can conclude that for alkaline earth metal cations of smaller and/or equal size than the Ca 2þ ions, the [SbFe(PO 4 ) 3 ] À Nasicon framework seems to be the most stable.…”
Section: Rietveld Refinement and Structural Description Ofmentioning
confidence: 79%
See 1 more Smart Citation
“…Diffraction lines with I obs < 1 are omitted. relationships between composition and crystal structure [20]. Indeed we can conclude that for alkaline earth metal cations of smaller and/or equal size than the Ca 2þ ions, the [SbFe(PO 4 ) 3 ] À Nasicon framework seems to be the most stable.…”
Section: Rietveld Refinement and Structural Description Ofmentioning
confidence: 79%
“…In fact, their structure is strongly dependant to the nature and/or size of the A II and M IV cations. More recently the relationships between composition and crystal structure of some A II-M IV (PO 4 ) 2 compounds were established [20]. Thus, Morin et al have shown that the structure of PbSn(PO 4 ) 2 (space group P2 1 /n) is related to the yavapaiite type but the lead atoms are located in zigzag tunnels instead of layers [10].…”
Section: Introductionmentioning
confidence: 99%
“…If the crystal remains reasonably homogeneous and robust despite the lack of crystallinity and ingrowth of decay products, this method could be viable. Tetravalent actinides, such as Np and Th can be synthesized as a cheralite analogue (M 2+ M' 4+ )(PO 4 ) 2 [18]. Testing is required to determine if the cheralite analogue is sufficiently homogeneous to serve as a microprobe reference material.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…Depending on the relative A and B-site ionic radii, the anhydrous alums may crystallize in either rhombohedral, trigonal, or monoclinic structures. In the monoclinic case, the B-site magnetic ions form an anisotropic triangular lattice as illustrated in Fig.1, whilst in the other two cases, an isotropic (equilateral) triangular lattice is realised 5 . Given this, as well as their chemical flexibility, a range of low-dimensional, frustrated, and anisotropic models can potentially be re-alized in the anhydrous alums.…”
Section: Introductionmentioning
confidence: 99%